Releasing Leadership Brilliance : Breaking Sound Barriers in Education. - Bailey, Simon T. (SAGE Publications, 2017)
What separates good leaders from brilliant ones? How do you successfully move your school or district from mediocrity to brilliance? Drawing on their expertise in business and education, the authors provide a simple, sustainable framework that will help you overcome educational inertia to reach new heights of achievement. The authors use the forces of flight as a powerful metaphor: Weight: Discover your Personal Brilliance through self-discovery Lift: Engage Collaborative Brilliance through collaboration with all stakeholders Thrust: Drive Team Brilliance by encouraging smart risks and designi.